Potencial de armazenagem de dois híbridos de canola submetidos as deteriorações artificial e natural - Coimbra, Ladislau Beims (2013)
Storage is a key step for the maintenance of seed quality. Canola (Brassica napus L.) must present, as all any other seeds, quality parameters for its commercialization, which can represent up to 10% of the production cost. The knowledge of Canola potential storage is a tool for its rational management. Therefore, the objective of this study was to evaluate the potential for storage of two seed hybrids of Canola (Hyola 433 and 411) in comparison with the controlled deterioration test in order to predict the potential of stored seeds. Physical-chemical, biochemical and physiological analysis of the seeds were conducted in three storage times (00, 30, 60 and 90 days) submitted to four different air relative humidity (HR) (20, 40, 70 and 100%), and to a controlled deterioration condition (seeds with 20% moisture content, at 45oC for 36h). We determined: percentage, speed and mean time of germination, shoot length, radicle length, total length of plantlets, number of dead and abnormal plantlets, moisture content, weight of a thousand seeds, electrical conductivity, content of lipid and protein, enzymatic activity of peroxidase and polyphenoloxidase, full breath (sensitive and insensitive to KCN). The experimental design was randomized and analyzed in a factorial design. The variables were expressed by polynominal regression. In general, all variables were affected by HR as a function of storage time. Germination percentage, thousand seed weight, respiration sensitive and insensitive to KCN were inhibited at HR tested against time. The values of average speed of germination, electric conductivity, plantlets length and moisture content had a tendency to increase. The numbers of killed an abnormal plantlets were inversely proportional to the reduction of germination, having higher values when storage conditions were less favorable. The activities of peroxidase and polyphenoloxidase were inhibitted and increased with air relative humidity and time, respectively. These results were effective to indicate the physiological potential of the seeds. In the controlled deterioration test, we observed that the speed of germination, germination rate and total respiration at higher RH and the activity of polyphenoloxidase at lower RH were promising. Therefore, it is possible to adjust the aging artificial methodology to predict the storage potential.